Who is Ready to Change Illicit Drug Use Behavior: An Emergency Department Study - Kenneth A. Frausto; Shahrzad Bazargan-Hejazi (SAGE Publishing, 2009)
Objective: To identify emergency department patients who are ready to change their illicit drug use behavior. Methods: A cross-sectional study of 198 Emergency Department patients at least 18 years old, seeking emergency department services, using at least one illicit drug, and scoring positive for alcohol problem based on CAGE score ≥ 1. Results: Of the patients, 46% were "not ready" to change their drug behavior, 21% and 33% were "unsure" and "ready", respectively. Our results identified that "Readiness to change alcohol behavior" [t (197) = 3.37, p ≤ 0.001], health insurance [t (197) = -3.011, p ≤ 0.003], number of drug use [t (197) = 2.88, p ≤ 0.004], and drug-related injury [t (197) = 1.98, p ≤ 0.049] were related to readiness to change illicit drug behavior. Conclusion: Our results re-iterate the need for intervention programs that focus on screening and treatment for both drugs and alcohol.